Examining social support and psychological well-being differences among youth across various sports - Abdul Latif, Rozita; Tumijan, Wahidah; Abdul Majeed, Hasmiza (Faculty of Sports Science and Recreation, 2025)
Social support and psychological well-being interrelated where various forms of assistance and care within the social network will encompass positive emotions, self-acceptance, and personal growth in youth sports. However, further research is needed to determine how social support and psychological well-being differ across different sports to tailor support effectively and maximize the mental health benefits for young athletes. The cross-sectional research design and an anonymous online survey to collect data from 298 SUKMA athletes in Negeri Sembilan was performed. The questionnaires used to measure social support was The Multidimensional Scale of Perceived Social Support (MSPSS) and psychological well-being was Psychological Well-being Scale. It involved Autonomy, Environmental Mastery, Personal Growth, Positive Relations with Others, Purpose in Life, and Self-Acceptance subscales. The independent t-test was computed to examine the differences between social support and psychological well-being between types of participation in sports. There was a significant disparity in social support between different types of sports among athletes [t(296)=2.82, p=0.005]. The difference in the level of Significance Others between individual (mean=5.45, SD=1.38) and team sports (mean=4.97, SD1.79) was significant, t(296)=2.66, p=0.008. The family support significant difference between individual sports (mean=5.57, SD=1.31) and team sports (mean=5.05, SD=1.71), t(296)=2.99, p=0.003. The individual athletes (mean=5.31, SD=1.39) reported a substantially higher level of agreeableness compared to team sports (mean=4.92, SD=1.72) in terms of friend support, t(296)=2.12, p=0.035. There was no significant difference in environmental mastery between individuals (mean=14.40, SD=2.76) and team sports (mean=14.05, SD=2.18), t(296)=1.17, p=0.243. While other parameters of psychological well-being indicated the statistical significance of the results among various types of sports. Team sports, on the other hand, encourage people to work together and help each other, but they may limit people's chances to achieve personal goals and grow as individuals by putting more emphasis on group goals and social interaction.